Restoration of severely damaged endodontically treated premolars: The influence of the endo-core length on marginal integrity and fatigue resistance of lithium disilicate CAD-CAM ceramic endocrowns - Rocca, G T; Daher, R; Saratti, C M; Sedlacek, R; Suchy, T; Feilzer, A J; Krejci, I (Journal of dentistry, 2018)
OBJECTIVES: To explore fatigue limits of ceramic endocrowns for premolars. METHODS: Forty-eight devitalized premolars were cut at the CEJ. They were restored with standardized CAD-CAM lithium disilicate reinforced ceramic restorations (IPS e.max CAD, Ivoclar-Vivadent) and divided into four Groups (n=12): overlays (Group A, no endo-core, negative control), endocrowns with an endo-core of 2mm (Group B), 4mm (GroupC) and crowns with post and core (Group D, positive control). All specimens were first submitted to thermo-mechanical cyclic loading (TCML)(1.7Hz, 49N, 600000 cycles, 1500 thermo-cycles). Margins were analysed before and after the loading. Survived specimens were then submitted to cyclic isometric stepwise loading (5Hz, 200N to 1200N) until completion of 105000 cycles or failure. In case of fracture, fragments were analysed using SEM and failure mode was determined. Results of stepwise loading were statistically analysed by Kaplan-Meier life survival analysis and log rank test (p=0.05). RESULTS: All the specimens survived the TCML test except four specimens of Group A (early restorations' debonding). No difference in percentages of closed margins was found between endocrowns (Groups B, C) and crowns (Group D). After the stepwise test, differences in survival within the groups were not statistically significant. Most of restorations experienced non-reparable fracture. CONCLUSIONS: Endocrowns with both 2-mm and 4-mm long endo-cores displayed outcomes after fatigue equivalent to classical crowns. Results of this study discourage the use of flat overlays with only adhesive retention. CLINICAL SIGNIFICANCE: When restoring extremely destroyed devitalized premolars, adhesive strategies should be coupled to a macro-mechanical retention in the root.
Keywords: Dental Porcelain; pevnost v tlaku; zubní porcelán; Dental Prosthesis Design; Endodontically treated; Marginal integrity; zubní materiály; Dental Marginal Adaptation; výsledek terapie; Tooth Cervix; design s pomocí počítače; Ceramics; zubní korunky; zubní marginální adaptace; lidé; Fatigue; Dental Restoration Failure; Survival Analysis; Computer-Aided Design; zubní krček; Treatment Outcome; zuby neživé; analýza zatížení zubů; Bicuspid; mechanický stres; Lithium disilicate; cementování; premolár; Stress, Mechanical; Materials Testing; keramika; trvalá zubní náhrada; Endocrown; zubní protéza - design; Cementation; Compressive Strength; Crowns; Dental Restoration, Permanent; Dental Materials; testování materiálů; analýza přežití; Dental Stress Analysis; Endo-core; Tooth, Nonvital; zuby-sanace - selhání; CAD-CAM; Humans